Mechanistic study on foam lamellae flow characteristics in tubes. (May 2015) - Du, D.; Zhang, J.; Sun, S.; Zhang, N.; Wang, D.; Li, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> For understanding foam propagation behaviour in porous media, experimental investigations were carried out concerning lamellae foam flow characteristics in a vertical tube. Foam is treated as a two-phase fluid, and the governing non-dimensional parameters were obtained through theoretical analysis. Two types of foams, CO2 and N2 foams, were studied and clear linear relationships between non-dimensional parameters of Δpd/σ and (3μU/σ)2/3 were observed. With different threshold values, the experimentally obtained mechanistic models for both foams predict much higher flow resistance compared with present popular models. Experimental results reveal the fact that a startup pressure is necessarily needed for mobilising the foam lamellae, and therefore indicate that the Herschel–Bulkley model instead of the power-law model could be better in revealing the mechanism of flowing foams in porous media in large scale.